ANALISIS KOMPARATIF CINTA MENURUT TEORI TRIANGULAR ROBERT STERNBERG DALAM THE GREAT GATSBY DAN TENGGELAMNYA KAPAL VAN DER WIJCK - Wajdi, Fathullah; Syawal, Sahrul; Ishak, Suryadi (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
Sternberg’s Triangular Love theory (1986) is used to examine love’s intricacy in The Great Gatsby (Fitzgerald, 1925) and Tenggelamnya Kapal Van Der Wijck (Hamka, 1939). The imbalance of passion, closeness, and commitment and culture’s impact on relationships are the primary issues. Comparing the three components in Western and Eastern civilizations was the goal. We employed qualitative textual analysis to analyze important quotes and storylines from both novels. Results: (1) Gatsby-Daisy has illusory desire without intimacy or actual commitment, while Zainuddin-Hayati has normative commitment and repressed passion. (2) Individualistic and communal cultures regulate the imbalance. The analysis shows that societal pressures and love imbalances cause the catastrophic conflicts in both works. This work advances Sternberg’s theory in comparative literary analysis.